Repository Istituzionali Open Access e strategie Linked Open Data Per una migliore comunicazione dei prodotti della ricerca scientifica - Solodovnik, Iryna (Strumenti per la didattica e la ricerca, 2015)
The purpose of this book is to highlight the relevance of the international Open Access (OA) movement, which aims at supporting and promoting strategies for the dissemination of scientific research products with the support of network technologies and open access policies. The OA Institutional Repositories (IRs) will be presented within the framework of: some guidelines, research evaluation mechanisms, intellectual property issues, long-term storage, Data and Process Management Plan and Trusted Digital Repositories. The work will also present a survey on a sample of 23 (Italian and international) digital repositories in support of communication and of open access to online research content. On the basis of this investigation, a ToolKit will be presented which could be useful for programming and monitoring several different features of an IR. Subsequently, the reader will be presented with a metadata scheme for the description of the scientific research products in IRs, which takes into consideration the Guidelines for the creation and management of metadata in Institutional Repositories (CRUI, 2012) and the Linked Open Data-enabled Bibliographical Data Recommendations (Subirats, Zeng, 2015). Metadata enabled as limit of detection (LOD) data will play a key role in qualifying the semantic profile of the properties of the considered metadata and, consequently, of the information resources they represent. They will also contribute to the enhancement of semantic interoperability and to the online promotion of collaborative dynamics of scientific research content on an Italian and international level, strengthening the effectiveness and efficiency of research itself.